2015
DOI: 10.5897/ajest09.171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NPK fertilizer on the shoot growth of Vitellaria paradoxa C.F. Gaertn.

Abstract: This study examined the effects of different levels of NPK fertilizer on the growth of Vitellaria paradoxa. Shoot height, collar diameter and leaf productions were assessed fortnightly up to the sixteenth week after transplanting. The results showed that there were no significant differences (P < 0.05) among the treatments in shoot height, collar diameter and leaf production. It was observed that shoot height of Vitellaria paradoxa exhibited close values ranging from 8.49 to 10.64 cm. The leaf production range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
1
0
3
Order By: Relevance
“…This conforms to the report of Aiyeloja and Azeez (2010) who noted that the total heights of S. setigera seedlings were not significantly affected by the type of fertilizer used. Yakubu et al (2015) also obtained a similar result for Vitellaria paradoxa. The authors reported that there was no significant difference in seedling height growth of V. paradoxa at 5% level of probability when different fertilizers were used.…”
Section: Treatmentssupporting
confidence: 61%
“…This conforms to the report of Aiyeloja and Azeez (2010) who noted that the total heights of S. setigera seedlings were not significantly affected by the type of fertilizer used. Yakubu et al (2015) also obtained a similar result for Vitellaria paradoxa. The authors reported that there was no significant difference in seedling height growth of V. paradoxa at 5% level of probability when different fertilizers were used.…”
Section: Treatmentssupporting
confidence: 61%
“…Six mois après semis, les jeunes plants de karité ont une croissance aérienne extrêmement lente telle que décrite par Dianda et al (2010) et Yakubu et al (2015). Cette croissance lente est au profit d'un développement racinaire important.…”
Section: Effet De La Provenance Et De La Fertilisation Sur La Croissaunclassified
“…Vitellaria paradoxa (le karité) est un arbre de la zone soudano-sahélienne (Yakubu et al, 2015). Il y a deux sous espèces de V. paradoxa dont l'une (V. paradoxa) s'étend du Sénégal vers l'Est jusqu'à la République Centrafricaine tandis que l'autre (V. nilotica) se rencontre dans le Sud du Soudan, en Ethiopie, en Ouganda et dans le Nord Est du Zaïre (Yakubu et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Vitellaria paradoxa commonly referred to as the shea butter tree is of the family Sapotaceae, and grows well in the savannah region of West Africa. The tree is of great economic importance due to its multipurpose use (Yakubu et al, 2015). It serves as a fruit tree as well as an oil seed crop.…”
Section: Introductionmentioning
confidence: 99%